The Problems of Using Online Dictionaries For Students of The Arabic Language Education Program, Bengkulu State Islamic University - Akhirudin, Akhirudin; Febriyani, Ade Irma; Hidayaturrahman, M. Hidayaturrahman (UIN Syekh Wasil Kediri, Indonesia, 2021)
This study aims to identify problems using the dictionary online and how to solve these problems in the Program for the Study of Arabic Language Education, at the Islamic State University of Bangkulu. This study uses qualitative research methods with interview data collection and documentation techniques. Students teaching Arabic at the Islamic State University of Bangkulu participated in the study The use of data analysis technology in this study is descriptive analysis of qualitative data: data reduction, data presentation and conclusion results.Search results show that 1) problems that have been addressed in the use of the Arabic dictionary on the Internet in teaching Arabic is, the Arabic dictionary on the Internet can not translate one paragraph at a time, then there can be another problem related to the Internet that is not good. 2) Dealing with problems using the Arabic dictionary online in teaching Arabic is using many of the online dictionary more effective to use, or another online dictionary or asking directly to people who understand its meaning.